SISTEM PEWARISAN PENARI ROL DALAM WAYANG ORANG PANGGUNG - Mr. Dr. Hersapandi,SST.,MS. (Joged, 2012)
The system of inheritance in the puppet stage appears to face a popular issue on the values ofprofessionalism that demands self-discipline and commitment to wrestle in total. Inheritance takes place intwo categories, namely: the first category that the inheritance according to the direct lineage or a child ofthe dancer roller. The second category, the inheritance of acquired dancer roller which is not the biologicalparent, but as a senior where he played the puppet people. Although they were aware that the dancer rolleris never created because it is considered as a replacement actor rivalry. A top dancer is an individual who has a mastery of knowledge and the quality of the high technicalskills, and be able to incarnate into a figure that was delivered. The top dancer transmission regeneration inthe context of the puppet stage is a must propesional profession in building a public figure image as aniconic of audience appeal. Keywords: top dancer, professional, icons appeal, inheritance